ANALISIS KRITIS TERHADAP PENGGUNAAN NYANYIAN ROHANI KONTEMPORER DI IBADAH MINGGU SORE GEREJA HKBP PARDAMEAN PEMATANG SIANTAR - Harminto Sihombing (Manna Rafflesia, 2023)
Generally, the songs for worship at the HKBP church come from the Buku Ende HKBP and Kidung Jemaat. However, a new phenomenon has emerged recently, especially in HKBP churches in urban areas, such as HKBP Pardamean Pematang Siantar, implementing Sunday services with a contemporary spiritual song. The signing has been made as long as possible among Pastors, assemblies, and congregations. Some parties agreed, and others disagreed. On the one hand, HKBP appreciates its repertoire of singing traditions, namely the Ende Book. But on the other hand, the HKBP church cannot avoid listening to contemporary churches in worship. Research on Sunday Evening Worship at HKBP Pardamean in this paper aims to produce constructive recommendations to answer all of that. This research will be conducted using a descriptive qualitative approach allowing the author to provide a broad explanation of using a contemporary spiritual course at HKBP Pardamean Pematang Siantar.